Analysis of High-, Intermediate-, and Low-Volume Surgeons When Performing Hysterectomy for Uterovaginal Prolapse. Issue 1 (January 2016) - Morgan, Daniel M.; Pulliam, Samantha; Adam, Rony A.; Swenson, Carolyn; Guire, Kenneth; Kamdar, Neil; Guaderrama, Noelani
Abstract : Objectives: To determine if surgeon volume is associated with differences in the use of apical colpopexy and cystoscopy and in the rate of intraoperative complications during hysterectomy for prolapse. Methods: We performed a multicenter retrospective review of hysterectomies done for uterovaginal prolapse at 4 hospital systems between January 1, 2008, and December 31, 2011. Low (⩽10 cases)-, intermediate (11–49 cases)-, and high (≥50 cases)-volume surgeon groups for the 4-year period were established a priori. Rates of concomitant colpopexy, cystoscopy, and intraoperative complications were determined by chart review for 15% of the cases. Multivariate logistic regression models adjusted for site and other clinical and patient variables were used to estimate associations between surgeon case volume and the use of apical colpopexy and cystoscopy and the rate of intraoperative complications. Results: Three hundred one surgeons performed 4238 hysterectomies for prolapse during the study period. Six hundred thirty-eight patients were selected for chart review. The rates among high-, intermediate-, and low-volume surgeons for performing colpopexy were 85.2% versus 77.8% versus 61.1% ( P < 0.001) and for cystoscopy were 96.8% versus 78.3% versus 74.7% ( P < 0.001), respectively. Rates of intraoperative complications among the 3 groups were 4.4%, 11.6%, and 6.3% ( P = 0.011), respectively. With adjustment, high-volume surgeons were more likely to do a colpopexy than low-volume surgeons (odds ratio [OR], 1.9; 95% confidence interval [CI], 1.1–3.1); however, the likelihood of colpopexy did not differ between high- and intermediate-volume surgeons (OR, 1.9; 95% CI, 0.84–4.3) or between intermediate- and low-volume surgeons (OR, 0.99; 95% CI, 0.50–2.0). High-volume surgeons were more likely than intermediate-volume (OR, 4.4; 95% CI, 1.7–11.0) and low-volume (OR, 4.5; 95% CI, 2.6–8.0) surgeons to do a cystoscopy. High-volume (OR, 0.42; 95% CI, 0.30–0.61) and low-volume (OR, 0.32; 95% CI, 0.15–0.66) surgeons were less likely than intermediate-volume surgeons to have intraoperative complications. The difference between high- and low-volume surgeons was not statistically significant (OR, 0.77; 95% CI, 0.5–1.2). Conclusions: Practice patterns with respect to hysterectomy for prolapse are complex when the use of colpopexy and cystoscopy and rates of intraoperative complications are analyzed by surgeon volume. The finding that intermediate-volume surgeons have the highest rates of intraoperative complications suggests a nonlinear relationship between surgeon volume and avoidance of injury. Abstract : Practice patterns during hysterectomy for prolapse are complex when the use of colpopexy and cystoscopy and rates of intraoperative complications are analyzed by surgeon volume.